O campo das ONG/AIDS: etnografando o ativismo em João Pessoa - Carvalho, Atila Andrade de (2012)
This thesis seeks to understand the formation of a specific sphere within the fight against AIDS: the field of NGO / AIDS. For this we investigated the relationship between social activism and strategic arrangements involving NGO / AIDS. To analyze this relationship is of vital importance for understanding the genesis of the socio - political NGO, which involves features and modes of action related to the particular situation and the historical context in Brazil and in Joao Pessoa. We use three theoretical concepts - analytical: activism, field and habitus. Using them could verify a variety of conditions which would be the profile of an NGO and activism, as legitimate or not taken in the construction of non-governmental responses to HIV / AIDS. We observed the forms of institutionalization of the field and the disputes it. Still we glimpse aspects of training of institutional and individual actors. The relationship between NGOs in the field of intersectoral / AIDS was observed from two perspectives: NGOs / NGOs and NGO / state. With this work we intend to contribute to knowledge on the current NGO movement / AIDS in Brazil from the presentation of a case: the field of NGOs / AIDS in Joao Pessoa. The methodology used and made by participant observation as a means of experiencing the meanings in the search field, and semi - structured interviews conducted individually with the activists in order to map the discussions and conflicts present in the scene, enabling us to better understand widely in the environment in formed the profiles of activism in the field of NGO/AIDS.